A Uniquely Important Napoleonic Memorial Sword. (2nd January 2018) - Rimer, Graeme
Abstract : This remarkably fine sword was commissioned by General Baron Gaspard Gourgaud, the close personal aide of Napoleon Bonaparte, to commemorate the return of the Emperor's body from St Helena to Paris in 1840. It was designed and made in 1842 by Alexandre Lapret, a distinguished artist-craftsman working in the famous Paris atelier of Henri Lepage.